2016
DOI: 10.2147/tcrm.s110464
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk factors in total thyroidectomy of substernal goiter

Abstract: The definition of substernal goiter (SG) is based on variable criteria leading to a considerable variation in the reported incidence (from 0.2% to 45%). The peri- and postoperative complications are higher in total thyroidectomy (TT) for SG than that for cervical goiter. The aim of this study was to evaluate the preoperative risk factors associated with postoperative complications. From 2002 to 2014, 142 (8.5%; 98 women and 44 men) of the 1690 patients who underwent TT had a SG. We retrospectively evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The quality of all included studies was assessed using the NOS, of which 10 studies were rated as high quality (four with 8 stars and six with 7 stars) and 13 studies were rated as moderate quality (11 with 6 stars and two with 5 stars) (Table 1). 3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] According to the heterogeneity for the meta-analyses on preoperative vitamin D levels (I 2 ¼ 74%, P ¼ 0.010), preoperative PTH (I 2 ¼ 92%, P < 0.0001) and preoperative calcium levels (I 2 ¼ 79%, P < 0.0009), a random-effects model was used for the meta-analyses. According to the heterogeneity for the meta-...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The quality of all included studies was assessed using the NOS, of which 10 studies were rated as high quality (four with 8 stars and six with 7 stars) and 13 studies were rated as moderate quality (11 with 6 stars and two with 5 stars) (Table 1). 3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] According to the heterogeneity for the meta-analyses on preoperative vitamin D levels (I 2 ¼ 74%, P ¼ 0.010), preoperative PTH (I 2 ¼ 92%, P < 0.0001) and preoperative calcium levels (I 2 ¼ 79%, P < 0.0009), a random-effects model was used for the meta-analyses. According to the heterogeneity for the meta-...…”
Section: Resultsmentioning
confidence: 99%
“…Two studies analysed the influence of substernal multinodular goitres. 24,27 Patients with substernal multinodular goitres showed a higher risk of postoperative hypocalcaemia (P ¼ 0.02, OR ¼ 1.70, 95% CI 1.09, 2.64) (Figure 12). Two studies analysed the influence of thyroiditis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated predictive factors of hypocalcemia after TT in order to anticipate therapy so as to reduce symptoms and guarantee a timely and safe discharge [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medial sternotomy is typically indicated in cases in which substernal extent of the gland goes beyond the aortic arch or the tracheal carina. When compared to removal of cervical goiters, patients undergoing removal of SSG were found to have higher perioperative morbidity and generally require longer hospital stays [5]. The most common complications of thyroid surgery include hematoma, recurrent laryngeal nerve injury, transient post-operative hypocalcemia and permanent hypoparathyroidism [1].…”
Section: Introductionmentioning
confidence: 99%
“…Bove et al additionally found that recurrence and extension of the goiter beyond the carina were statistically signifi cant pre-operative risk factors associated with higher risks of complications. They considered growth of the glandbeyond the level of the carina to be a more signifi cant risk factor than the volume of the gland itself[5].…”
mentioning
confidence: 99%